Longitudinal validity and prognostic significance of the St George's Respiratory Questionnaire in Mycobacterium avium complex pulmonary disease. (August 2021) - Ogawa, Takunori; Asakura, Takanori; Suzuki, Shoji; Okamori, Satoshi; Kusumoto, Tatsuya; Sato, Yasunori; Namkoong, Ho; Kamata, Hirofumi; Ishii, Makoto; Fukunaga, Koichi; Hasegawa, Naoki
Abstract: Background: Although previous cross-sectional studies showed the feasibility and clinical association of the St. George's Respiratory Questionnaire (SGRQ) in Mycobacterium avium complex pulmonary disease (MAC-PD), its longitudinal validity is poorly understood. We aimed to determine the longitudinal validity and prognostic significance of SGRQ. Methods: In this prospective observational study conducted between May 2012 and August 2018, we evaluated 269 enrolled patients with MAC-PD and examined associations between baseline SGRQ total scores and mortality or clinical variables (anchors), including serum C-reactive protein levels and pulmonary function test results. Results: Age- and sex-matched SGRQ scores indicated significantly greater impairment in patients with MAC-PD than in the general population ( P  < 0.001). On multivariable Cox proportional hazards regression analysis, the SGRQ total score ≥25 was an independent risk factor for mortality (adjusted hazard ratio, 5.90; 95% confidence interval, 1.65–37.7) as well as age, body mass index, and forced vital capacity (FVC). Mixed-effect model results showed a significant association between SGRQ symptom/total scores and forced expiratory volume in 1 s (FEV1 ), FVC, and diffusing carbon monoxide capacity. Older age, a positive smear, non-nodular/bronchiectatic form, and cavity regions were associated with SGRQ total score deterioration. Patients with a greater decline from baseline FEV1 (% predicted) exhibited significantly worse impairment in the SGRQ total score (mean ± SE, 4.69 ± 10.9 points, P  = 0.001). Conclusions: SGRQ showed longitudinal validity in assessing disease severity and was sensitive to changes in patients with MAC-PD, especially changes in %FEV1. The SGRQ total score may be an important prognostic factor. Highlights: We investigated the longitudinal validity of SGRQ scores in patients with MAC-PD. Changes in PFTs were significantly associated with those in SGRQ scores. Older age, smear+, non-NB form, and cavity predicted the decline of SGRQ scores. The SGRQ total score ≥25 was an independent risk factor for mortality.